The transporter factsbook - Griffith, Jeffrey (Factsbook series., 1998)
How do you keep track of basic information on the proteins you work with? Where do you find details of their physicochemical properties, amino acid sequences, and structure? Are you tired of scanning review articles, primary papers, and databases to locate that elusive fact? The Academic Press FactsBook Series has established itself as the best source of easily-accessible and accurate facts about protein groups. Described as "a growing series of excellent manuals" by Molecular Medicine Today and "essential works of reference" by Trends in Biochemical Sciences, the FactsBooks have become the most popular comprehensive data resources available. Using an easy-to-follow format, the FactsBooks will keep you up-to-date with the latest advances in structure, amino acid sequences, physicochemical properties, and biological activity. Meticulously researched and compiled by experts in the field, keeping abreast of developments has never been so easy! The Transporter FactsBook contains entries covering almost 800 transporters. Organized into 55 families of structurally related transporters, this volume includes ATPases, ABC transporters, H+-dependent antiporters and symporters, Na+-dependent antiporters and symporters, and other transporters such as mitochondrial transporters. Key Features * Nomenclature, biological sources and substrates * Phylogenetic relationships * Predicted structures * Physical and genetic characteristics * Multiple amino acid sequence alignments * Database accession numbers * Key references